2018
DOI: 10.1177/0361198118773199
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Assess the Quality of Travel Time Estimation and Incident Detection Based on Connected Vehicle Data

Abstract: Connected vehicle (CV) technologies are expected to have a significant influence on the investment decisions of transportation system management and operations (TSMO) in the near future. One of the potential applications is the use of CV data to support various TSMO processes. This study investigates the use of CV data as an alternative to existing data acquisition techniques in providing two critical functions to support TSMO: travel time estimation and incident detection. In support of this investigation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…An important input to the calculation of delay in the above equations is the reduction in the incident duration due to the reduction in the detection time resulting from applying the alternative detection technology. The incident detection time based on CV data and traffic detector were derived based on simulation results by the authors of this study, as shown in Equations 4 and 5, respectively ( 25 , 26 ):…”
Section: Methodolgymentioning
confidence: 99%
See 1 more Smart Citation
“…An important input to the calculation of delay in the above equations is the reduction in the incident duration due to the reduction in the detection time resulting from applying the alternative detection technology. The incident detection time based on CV data and traffic detector were derived based on simulation results by the authors of this study, as shown in Equations 4 and 5, respectively ( 25 , 26 ):…”
Section: Methodolgymentioning
confidence: 99%
“…where l = Arrival rate (demand) (vph) m = Arrival rate (demand) (vph) m R = Reduced capacity rate under metering for ramps or under non-recurrent conditions for the mainline (vph) t R = Event duration (hr) t Q = Time in queue duration (hr) An important input to the calculation of delay in the above equations is the reduction in the incident duration due to the reduction in the detection time resulting from applying the alternative detection technology. The incident detection time based on CV data and traffic detector were derived based on simulation results by the authors of this study, as shown in Equations 4 and 5, respectively (25,26):…”
Section: Npv Analysismentioning
confidence: 99%
“…Iqbal et al [ 30 ] evaluated the application of basic safety messages (BSMs) obtained from the vehicle-to-vehicle (V2V) communication environments of connected vehicles (CVs) for travel time estimations and incident detection. Regression models were used to estimate vehicle travel times.…”
Section: Introductionmentioning
confidence: 99%
“…The review of the literature indicated that the application of V2I probe data for automatic incident detection had not been previously investigated. Iqbal et al [ 30 ], and Wolfgram et al [ 31 ] utilized basic safety messages (BSMs) obtained from the vehicle-to-vehicle (V2V) communication environments for automatic incident detection. However, to the best of the authors’ knowledge, this paper is the first study to propose an automatic incident detection algorithm on the basis of V2I probe data.…”
Section: Introductionmentioning
confidence: 99%